GRATITUDE AND ISLAMIC SPIRITUAL INTELLIGENCE AS SOCIAL WELFARE CAPITAL: A STUDY ON INNER PEACE AMONG ISLAMIC COUNSELING AND GUIDANCE STUDENTS AT UIN SUMATERA UTARA - Amanda, Friska; Arifin, Zainal (Jurnal Al-Ijtimaiyyah, 2026)
Students' social welfare is an important part of Islamic community development, since psychological stability shapes the quality of their social contribution on campus and in wider society. High academic pressure can disrupt this welfare, making psychological-spiritual capital such as gratitude essential for students' inner peace, including for students of the Islamic Counseling and Guidance Study Program (BPI), Faculty of Da'wah and Communication, Universitas Islam Negeri Sumatera Utara (UINSU). This study analyzes the effect of gratitude within Islamic spiritual intelligence on students' inner peace as an indicator of social welfare. A quantitative approach with an associative-causal method was used. A total of 93 out of 248 students were selected as respondents through purposive sampling. Data were collected using a Likert-scale questionnaire tested for validity and reliability, then analyzed through classical assumption tests and simple linear regression using SPSS version 25. Results show that gratitude has a positive and significant effect on students' inner peace, with a significance value of 0.000 (p < 0.05) and a regression coefficient of 0.625. The coefficient of determination (R²) of 0.567 indicates that 56.7% of the variation in students' inner peace is explained by gratitude. These findings highlight the importance of strengthening gratitude and Islamic spirituality to develop students' social-psychological welfare within Islamic higher education.